Effects of a combined exercise program in muscle strength and functional capacity in a individual with Postpoliomyelitis syndrome: case report - Mota, Cristiane Gonçalves; Silva, Susana Cristina Oliveira; Teixeira, Barbara Vilar; Oliveira, Fernanda Melo; Cardoso, Cristiane Vieira (Acta Fisiátrica, 2018)
Postpoliomyelitis Syndrome is a enterovirus pathology, which predominantly damages the lower muscles, which cause flaccid and asymmetric muscle paralysis, based on lower and late neuromuscular and functional symptoms denominate Postpoliomyelitis Syndrome (PPS). Objective: To apply a combined exercise program and to verify the results on the muscle strength and functional capacity of an elderly individual with PPS. Methods: The sample was one women, 66 years old, with comorbities hypertension, dyslipidemia, hypothyroidism. Muscle strength was measured by 7 - 10 maximal repetitions (MR) test. The distance traveled pedaling was performed by Adapted 12-minute Test and the balance was evaluated by Timed Up & Go Test. The muscle strength training was intensity 60% of a one maximum repetition. Results: After 24 weeks, the muscular strength of lower limbs increased 333.3% and the upper limbs, 216.5%. The balance improved 34.3%. The distance traveled pedaling increased 11.8%. Conclusion: The results suggest that individuals with PPS, even if elderly, may benefit from an exercise program to increase muscle strength and improve functional capacity, but it is important that other studies are developed to verify these results in a larger number of individuals.